1975
DOI: 10.1139/z75-010
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics of Ixodes (Ceratixodes) uriae White, 1852 on auks (Alcidae) from Newfoundland

Abstract: Two hundred and fifty auks of five species (Alca torda, Uria aalge, Uria lomvia, Cepphus grylle, Fratercula arctica) were collected in Newfoundland in 1972 and 1973, and examined for Ixodes uriae. Ticks were recovered from all the bird species examined except C. grylle. No significant difference (P > 0.05) was found in the burden on adult auks with regard to sex and weight. The distribution of the tick stages on the hosts is presented: adult females prefer the neck, larvae prefer the body regions. The distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 0 publications
4
59
1
Order By: Relevance
“…1b). This tick reproduces sexually, and a female will lay between 200 and 600 eggs in a single bout before dying (Eveleigh & Threlfall 1975, Dietrich 2011. In new seabird colonies, tick populations tend to increase with colony size for approximately the first 30 yr, after which time the population dynamics seem to stabilise (Danchin 1992).…”
Section: Biological System and Sampling Sitesmentioning
confidence: 99%
“…1b). This tick reproduces sexually, and a female will lay between 200 and 600 eggs in a single bout before dying (Eveleigh & Threlfall 1975, Dietrich 2011. In new seabird colonies, tick populations tend to increase with colony size for approximately the first 30 yr, after which time the population dynamics seem to stabilise (Danchin 1992).…”
Section: Biological System and Sampling Sitesmentioning
confidence: 99%
“…They are usually associated with seabird colonies, and more than 50 species have been recorded as host of this ectoparasite (Wilson 1970;Eveleigh and Threlfall 1974;Bergström et al 1999). Tick eVects on the host include delay in chick growth (Morbey 1996), chick mortality (Chastel et al 1987;Bergström et al 1999) and even adult mortality (Gauthier-Clerc et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Biological model and specific predictions I. uriae commonly parasitises Black-legged kittiwakes in the northern hemisphere (eg, Eveleigh and Threlfall, 1974). This tick was considered to be a generalist parasite of seabirds, but recent genetic work has shown that hostassociated races, in particular for the kittiwake, do occur .…”
Section: Introductionmentioning
confidence: 99%
“…This tick was considered to be a generalist parasite of seabirds, but recent genetic work has shown that hostassociated races, in particular for the kittiwake, do occur . The life cycle of this parasite generally takes 4 years to complete and consists of three active stages: larva, nymph and adult (Eveleigh and Threlfall, 1974). In order to pass from one stage to the next, the tick must take a single blood meal on its host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation